Cholesterol-lowering properties of defatted kenaf seed meal and its phenolics-saponins-rich extract in a rat model - Chan, Kim Wei (2019)
Kenaf (Hibiscus cannabinus L.) is an important commercial fiber crop and defatted kenaf seed meal (DKSM) is a secondary by-product from the kenaf industry. The present study focused on the investigation of cholesterol-lowering properties of DKSM and its phenolics-saponins-rich extract (PSRE) in a rat model. Proximate analysis revealed that DKSM was high in protein, carbohydrate and crude fibre; while magnesium, potassium and phosphorus were the major minerals found in DKSM. The absence of acute oral toxicity in DKSM was observed through brine shrimp and rat models. In addition, DKSM exhibited higher phenolic content and antioxidant activity as compared to the selected edible flours (p < 0.05). Next, PSRE was prepared from refluxed extraction of DKSM and then fractionated with n-butanol to obtain butanolic (BF) and aqueous (AqF) fractions, which were respectively rich and deficient in phenolic-saponin content. BF was confirmed to exhibit the highest phenolicsaponin content and antioxidant activity, followed by PSRE and AqF (p < 0.05). Antioxidant activity of PSRE and its fractions were strongly correlated to their phenolic-saponin content, suggesting that phenolics and saponins may be the key bioactives that contribute to the antioxidant properties of DKSM and PSRE. Cholesterol-lowering properties of DKSM and PSRE were evaluated through a hypercholesterolemic rat model and dietary interventions were conducted by incorporating DKSM (15% and 30% of total diet) or PSRE (at 2.3% and 4.6% of total diet, respectively equivalent to the total content of DKSM-phenolics and saponins in the DKSM groups) into the atherogenic diets. After 10 weeks of DKSM and PSRE supplementation, the hepatosomatic index, hepatosteatosis, serum lipid profile, Castelli risk indexes and toxicity biomarkers of hypercholesterolemic rats were significantly improved (p < 0.05). Besides, the levels of hepatic Hmgcr and serum Pcsk9 were lowered, along with transcriptional upregulations of hepatic Cyp7a1, Abca1, Lcat, ApoA2 and ApoE (p < 0.05). The gene expression of hepatic Ldlr was insignificantly enhanced by DKSM (p > 0.05), but significantly upregulated by PSRE (p < 0.05). The combined results showed that hypercholesterolemia and atherogenic risk in rats were effectively attenuated by DKSM and PSRE supplementation, possibly via modulations of multiple vital processes in hepatic cholesterol metabolism. In addition, serum total antioxidant capacity and hepatic expression of antioxidant genes of hypercholesterolemic rats were significantly enhanced by DKSM and PSRE supplementation, accompanied with marked suppression against the levels of circulating oxidized low-density lipoprotein and pro-inflammatory biomarkers (p < 0.05). Apart from the potential beneficiary effects of alleviated hypercholesterolemia, DKSM and PSRE may attenuate hypercholesterolemiaassociated oxidative stress and systemic inflammation in rats by enhancing the serum total antioxidant capacity as well as the endogenous antioxidant defense via activation of hepatic Nrf2-ARE pathway. In conclusion, DKSM and itsderived PSRE are effective functional food ingredients in ameliorating hypercholesterolemia and its-associated oxidative stress and systemic inflammation in the rat model. Phenolics and saponins may be the bioactives conferring DKSM and PSRE with their cholesterol-lowering, antioxidative and anti-inflammatory properties.